1985
DOI: 10.1177/074193258500600507
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Self-Concepts of Handicapped Students

Abstract: The phenomenal and nonphenomenal self-concepts of 120 handicapped students (emotionally disturbed, educable mentally retarded, learning disabled, speech/language impaired) were compared to those of30 nonhandicapped students. The Piers-Harris Children's Self Concept Scale, a self reporting instrument, was used to assess phenomenal (conscious) attitudes toward the self. The Human Figure Drawing Test, a projective measure, was administered to assess nonphenomenal (unconscious) attitudes regarding the self The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Four studies compared the level of physical appearance self‐concept between youth with intellectual disabilities and TD youth (Table ). These studies focusing on samples of children attending a special school , and adolescents or children‐adolescents (Beck, Roblee, & Hanson, ; Jones, ) attending a special class did not find any significant difference.…”
Section: Resultsmentioning
confidence: 92%
“…Four studies compared the level of physical appearance self‐concept between youth with intellectual disabilities and TD youth (Table ). These studies focusing on samples of children attending a special school , and adolescents or children‐adolescents (Beck, Roblee, & Hanson, ; Jones, ) attending a special class did not find any significant difference.…”
Section: Resultsmentioning
confidence: 92%
“…However, results from these studies have been mostly inconclusive regarding possible differences between youth with L-CA and youth with A/H-CA. Indeed, whereas some studies reported lower self-esteem in adolescents with L-CA compared with their peers with A/H-CA (e.g., Chiu, 1990;Chovan & Morrison, 1984;Jones, 1985), other studies reported higher (e.g., Lemétayer & Kraemer, 2005;Ninot, Bilard, Delignières, & Sokolowski, 2000;Pierrehumbert, Zanone, Kauer-Tchicaloff, & Plancherel, 1988), or equivalent levels (e.g., Beck, Roblee, & Hanson, 1982;Carroll, Friedrich, & Hund, 1984;Huck, Kemp, & Carter, 2010). Methodological differences may partly explain some of these discrepant findings, such as possible differences in the gender and age compositions of samples across and within studies (i.e., whether the studies compared matched samples or convenience samples of youth with L-CA and A/H-CA), or lack of information regarding the psychometric properties of the self-esteem instruments used with adolescents with L-CA (Marsh, Tracey, & Craven, 2006;Nader-Grosbois, 2014;Tracey, Craven, & Marsh, 2015).…”
Section: Self-esteem Development In Adolescents With Low Levels Of Comentioning
confidence: 99%
“…The term ‘self‐concept’ accounts for a significant portion of achievement of measured intelligence, socio‐economic status, educational aspirations, and the expectations of family, friends and teachers (Brookover et al 1965; Jones 1985; Fitts 1972). Research on the self‐concept of persons with ID has been mostly connected with school achievement and educational setting, and results show that children with ID have a lower self‐concept than any other group (Jones 1985; Fitts 1996).…”
Section: Introductionmentioning
confidence: 99%